2020
DOI: 10.1080/00325899.2020.1829349
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental principles of spark plasma sintering of metals: part II – about the existence or non-existence of the ‘spark plasma effect’

Abstract: The mechanisms of densification in spark plasma sintering (SPS) were investigated both analytically and numerically for a model system of two spherical metallic powder particles. From the microscopic temperature distribution, the possibility of a micro-local overheating of the particleparticle contacts was analysed for different particle sizes, contact geometries, materials, and electrical loads. It is shown that, for particles below the size of one millimetre, local overheating is below one Kelvin. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…Analytical models [9,11,13,[18][19][20][21][22] play a key role in understanding of the sintering process, but drastic simplifications have to be assumed (e.g. oversimplified geometry, isothermal sintering and neglected grain growth) that limit their ability to quantitatively predict the densification of real powder compacts.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical models [9,11,13,[18][19][20][21][22] play a key role in understanding of the sintering process, but drastic simplifications have to be assumed (e.g. oversimplified geometry, isothermal sintering and neglected grain growth) that limit their ability to quantitatively predict the densification of real powder compacts.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that in works that have proposed excessive local overheating, a fundamental factor, which is heat dissipation by conduction inside the particles, has not been considered and the calculations have been performed in adiabatic conditions. Taking into account this factor in the calculations, the amount of temperature distribution within the particles in copper [104], TiAl [105], bismuth telluride [106], and steel particles [74] was evaluated. It was found that although the current density at the contact points of the particles can reach up to several thousand times higher than its average value in the sample, the heat conduction phenomenon is high enough to prevent a significant temperature gradient inside a particle [105].…”
Section: Pulsed Electrical Currentmentioning
confidence: 99%
“…In addition, temperature inhomogeneity inside the particle is directly proportioned to grain size, which means the finer the grain, the smaller the temperature difference between particle contact and particle center, and vice versa. Figure 6 demonstrates the effect of particle size and contact radius on the temperature inhomogeneity inside the Cu particle, which is called supertemperature [104]. As shown in Fig.…”
Section: Pulsed Electrical Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the use of pulsed DC current is believed to facilitate electric discharges at the points of powder contacts and grain boundaries, making any gaps in the compact act very similar to capacitors and hence fusing them into a monolithic solid at a faster rate when compared to conventional sintering methods . However, this is a topic of debate, and there is evidence as for negligible influence of pulsing rates and sparks . Furthermore, one must be very cautious when referring to sintering temperatures in SPS systems, given that it is not possible to measure the exact temperature of the powder compact at the time of sintering through direct measurements by a pyrometer or a thermocouple, especially at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%